Injuries from electronic cigarettes, and cigarette/cigar-related paraphernalia, NEISS, 2012-2022. - R Constance Wiener; Eric W Lundstrom (PLoS ONE)
There is a need to determine the role of smoking/vaping related products in Emergency Department (ED) product-related injuries by age and sex to determine if interventions are warranted. These products include the combustible tobacco products' paraphernalia to light them (CTPP), electronic nicotine delivery systems (ENDS), and electronic non-nicotine delivery system (ENNDS). Data from the National Electronic Injury Surveillance System (NEISS), years 2012-2022, were examined for injury data associated with CTPP and ENDS/ENNDS. Bivariate comparisons were conducted. There were an estimated 3,142 (95%CI: 2,384-3,975) ED-treated ENDS/ENNDS product-related injuries and 46,116 (95%CI: 38,712-53,520) CTPP product-related injuries. Males were more likely to have an ED-treated ENDS/ENNDS product-related injury than females (proportion 0.93 [95%CI: 0.82, 0.98] versus 0.70 [95%CI: 0.02, 0.19]) as well as a CTPP product-related injury than females (proportion, 0.60 [95%CI: 0.56, 0.64] versus 0.40 [95%CI: 0.37, 0.44]). There were more ED-treated ENDS/ENNDS product-related injuries among persons ≥18 years than <18 years (proportion, 0.89 [95%CI: 0.75, 0.96] versus 0.11 [95% CI: 0.4, 0.35]). There were also more ED-treated CTPP product injuries among persons ≥ 18 years than <18 years (proportion, 0.73 [95%CI: 0.68, 0.78] versus 0.27 [95%CI: 0.22, 0.32]). No change in the proportion of injuries in our sample associated with END/ENNDS over time were observed. There is a need to consider injuries related to ENDS/ENNDS and CTPP product-related injuries in the discussion of the risks associated with smoking/vaping. Although ENDS/ENNDS have had fewer ED-treated injuries, the number of such injuries has remained stable, rather than declined over the previous decade. Injury prevention is a public health imperative and targeted interventions by healthcare providers during routine care, and the use of public service announcements could specifically target adults ≥18 years. Providing peer-to-peer educational programs, and initiating similar programs targeted at males who use CTP and ENDS/ENNDS have the potential to decrease injury risk.